The Effect Of Cadres Training Contributed To Their Knowledge And Skill In Filling Out Kartu Menuju Sehat (KMS) At Puskesmas PAsir Putih In Kotawaringin Timur Regency - Lilis Murtutik (Jurnal Ilmu Keperawatan Indonesia (JIKI), 2017)
...